Learning Blender : a hands-on guide to creating 3D animated characters - Villar, Oliver (Addison-Wesley, 2017)
Master the Newest Blender Techniques for Creating Amazing 3D Characters: From Design and Modeling to Video Compositing Now fully updated for Blender 2.78b and beyond, Learning Blender, Second Edition, walks you through every step of creating an outstanding 3D animated character with Blender, and then compositing it in a real video using a professional workflow. This edition covers the powerful new selection and modeling tools, as well as high-efficiency improvements related to other parts of the project such as texture painting, shading, rigging, rendering, and compositing. Still the only Blender tutorial to take you from preproduction to final result, this guide is perfect for both novices and those moving from other software to Blender (open source and free software). Author Oliver Villar provides full-color, hands-on chapters that cover every aspect of character creation: design, modeling, unwrapping, texturing, shading, rigging, animation, and rendering. He also walks you through integrating your animated character into a real-world video, using professional camera tracking, lighting, and compositing techniques. The rich companion website (blendtuts.com/learning-blender-files) will help you quickly master even the most complex techniques with bonus contents like video tutorials. By the time you're done, you'll be ready to create outstanding characters for all media--and you'll have up-to-date skills for any 3D project, whether it involves characters or not. Learn Blender's updated user interface, navigation, and selection techniques Create your first scene with Blender and the Blender Render and Cycles render engines Organize an efficient, step-by-step pipeline to streamline workflow in any project Master modeling, unwrapping, and texturing Bring your character to life with materials and shading Create your character's skeleton and make it walk Use Camera Tracking to mix 3D objects into a real-world video Transform a raw rendered scene into the final result using Blender's compositing nodes.